Impact of chilling stress on quality and bioactive compounds in young and mature leaves of kratom [Mitragyna speciosa (Korth.) Havil.] - Supapvanich, Suriyan; Raruang, Yenjit; Promyou, Surassawadee (Agriculture and Natural Resources, 2024)
Abstract Importance of the work: There has been much attention paid to kratom (Mitragyna speciosa [Korth.] Havil.) since it was declared a legal plant in Thailand. Recently, the demand for fresh leaves has increased; nevertheless, only a few studies have investigated the postharvest quality management of the leaves. Objectives: To examine the impact of chilling stress on the quality and alteration of bioactive compounds in young and mature leaves of two cultivars of commercial kratom leaves: ‘kan khiao’ and ‘hang kang’. Materials and Methods: Fresh kratom leaves of both the kan khiao and hang kang types were sampled from the young and mature leaf stages and stored for 12 d with 85% relative humidity at: 1) 10°C or 2) at room temperature (RT;30°C) . Every 3 d throughout storage, monitoring occurred of the fresh weight loss, superficial leaf color, browning score, electrolyte leakage (EL), malondialdehyde (MDA) content and bioactive compounds (ascorbic acid, antioxidant activity, total phenolic compounds and mitragynine contents). Results: Chilling injury (CI; based on brown stain on the leaf) was discovered in both types of kratom leaves refrigerated at 10°C. In both types, RT storage resulted in less weight loss and browning. Yong leaves lost less weight loss and CI than mature leaves. CI was positively associated with increased EL and MDA levels in leaves kept at 10°C. In both types, the mitragynine content in the mature leaves was higher than in the young leaves. Both types lost mitragynine, ascorbic acid, antioxidant activity and phenolic compounds due to the cold storage condition. Main finding: Cold storage induced chilling stress that resulted in leaf browning due to membrane dysfunction, as well as the loss of bioactive compounds and medicinal components, including mitragynine.